الاتجاهات الرئيسية للتنمية وواقع التجربة التنموية الجزائرية - هويدي, عبد الباسط; قنوعه, عبد اللطيف (جامعة الوادي University of Eloued, 2014)
ي هذا المقال سنتناول الاتجاهات الرئيسية للتنمية، والنماذج التنموية في الدول المتقدمة والنماذج التنموية في الدول النامية. حيث عرضنا في النموذج الأول عدة اتجاهات أهمها: الاتجاه التطوري المحدث، اتجاه النماذج والمؤشرات، الاتجاه السيكولوجي، الاتجاه الانتشاري، ثم تحدثنا عن الماركسية الكلاسيكية وقضيا التنمية، ثم الماركسية المحدثة وقضيا التنمية، ثم تحدثنا عن التنمية في الدول النامية، كنموذج أمريكا اللاتينية، ونموذج الصين، ثم الجمع بين النموذجين في التجربة الهندية، ثم تحدثنا عن التنمية في الجزائر في مختلف مرحلها، سواء مرحلة ما قبل الانفتاح السياسي والاقتصادي أو مرحلة الانفتاح على النموذج الرأسمالي من جديد وتأثيرات هذا الانفتاح على التنمية الاجتماعية والاقتصادية In this article we will discuss the main trends of development, such as Models of development in developed countries and development models in developing countries. Where we offered in the first model a several directions, including: updated evolutionary direction, the direction of models and indicators, the psychological trend, the trend trickle-down, and then we talked about classical Marxism and spent a development, then spent the updated Marxism and development, then we talked about the development in developing countries, as a model for America Latin, and the China model, and then combine the two models in the Indian experience, and then we talked about the development in Algeria in various stage are, whether pre-political and economic openness stage or opening to the capitalist model of the effects of this new openness to social and economic development.
The main trends of development and the reality of the Algerian developmental experience
مقال- مجلة رؤى اقتصادية
Keywords: التنمية، الاتجاهات التنموية، السياسات التنموية، مخططات التنمية، الرأسمالية، ، الانفتاح الاقتصادي، الإصلاحات الاقتصادية; development, development trends, development policies, development plans, capitalism, economic openness, economic reforms.